Development, Modernization, and Childbearing - Filmer, Deon; Friedman, Jed; Schady, Norbert (World Bank, 2012)
Does the sex composition of existing children in a family affect fertility behavior? An unusually large data set, covering 64 countries and some 5 million births, is used to show that fertility behavior responds to the presence—or absence—of sons in many regions of the developing world. The response to the absence of sons is particularly large in Central Asia and South Asia. Modernization does not appear to reduce this differential response. For example, in South Asia the fertility response to the absence of sons is larger for women with more education and has been increasing over time. The explanation appears to be that a latent demand for sons is more likely to manifest itself when fertility levels are low. As a result of this differential fertility behavior, girls tend to grow up with significantly more siblings than do boys, with potential implications for their well-being when quantity–quality tradeoffs result in fewer material and emotional resources allocated to children in larger families.